Bone density of the calcaneus correlates with radiologic and clinical outcomes after calcaneal fracture fixation. Issue 8 (August 2020) - Lee, Sang Min; Seo, Jae Seung; Kwak, Sang Ho; Shin, Won Chul; Bae, Jung Yun; Woo, Seung Hun
Highlights: We found high correlations between hounsfiled unit values of the uninjured calcaneus on preoperative CT and BMD scores from DXA scans. Decreased preoperative bone density significantly correlated with decreased Böhler's angle and inferior short-term clinical outcomes. Preoperative information of bone density using CT may indirectly have a significant implication into treatment algorithms for DIACF Abstract: Background: This study aimed to determine whether bone density correlates with radiologic and clinical outcomes after screw fixation of displaced intra-articular calcaneal fractures (DIACF) with the sinus tarsi approach. Materials and methods: We retrospectively evaluated 43 consecutive cases of unilateral DIACF between March 2015 and December 2017. Radiologic evaluations were performed using preoperative, postoperative, and last follow-up calcaneal lateral and axial radiographs. In all patients, preoperative CT scanning of both injured and uninjured calcaneus were performed at one scanning and dual x-ray absorptiometry (DXA) scans were obtained. Hounsfield unit (HU) measurement values were determined by placing an elliptical region of interest confined to the cancellous region of the uninjured calcaneus. Clinical outcomes were assessed at a minimum of 12 months postoperatively using Foot and Ankle Outcome Scores (FAOS). Results: Mean HU values of the uninjured calcaneus significantly correlated with bone mineral density scores obtained from DXA scans of the lumbar and femur (Spearman ρ = 0.656 - 0.748; p < 0.001 for both). Decreased HU values of the uninjured calcaneus significantly correlated with decreased Böhler's angle and widening of calcaneal width from postoperative to last follow-up. (Pearson r = 0.348, p = 0.022; Pearson r = -0.582, p < 0.001, respectively). Increased HU values of the uninjured calcaneus significantly correlated with improved clinical outcomes in three of five FAOS domains, including activities of daily living, sports, and quality of life (beta = 0.283 - 0.322; p < 0.05 for all). Conclusion: Decreased preoperative bone density significantly correlated with decreased Böhler's angle, widening of calcaneal width, and inferior short-term clinical outcomes after screw fixation of DIACF. By quantifying bone density using HU value in area where DXA cannot be performed, such foot bones, determining whether different fixation methods or systemic treatments can be tailored to bone density could help in optimizing clinical outcomes. Level of Evidence: : Level III, Retrospective case series